2021
DOI: 10.1111/rda.13904
|View full text |Cite
|
Sign up to set email alerts
|

A field study using different technologies to detect calving at a large‐scale hungarian dairy farm

Abstract: The objective of this study was to investigate three different calving detection systems in order to assess and compare their efficiency. The study was conducted at a large‐scale dairy farm involving 54 Holstein‐Friesian dairy cows and heifers. Animals were fitted with multiple devices: a rumination measuring device (Ruminact® (RA)), an intravaginal thermometer (Vel’Phone® (VP)) and a tail movement sensor (Moocall® (MC)) 5 to 7 days before expected calving and were removed after parturition. RA detects ruminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
(51 reference statements)
1
16
0
Order By: Relevance
“…However, they reported that in a high temperature climate, the difference between internal and external temperature was sometimes not enough to generate the alert. Another intravaginal calving alarm device is the Medria Vel'Phone ® [21,24,40]. This system, which is equipped only with temperature sensors, can send two different alarms; the former is due to a physiological decrease in vaginal temperature around 48 h before calving, while the latter is due to the expulsion of the device at the beginning of labor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they reported that in a high temperature climate, the difference between internal and external temperature was sometimes not enough to generate the alert. Another intravaginal calving alarm device is the Medria Vel'Phone ® [21,24,40]. This system, which is equipped only with temperature sensors, can send two different alarms; the former is due to a physiological decrease in vaginal temperature around 48 h before calving, while the latter is due to the expulsion of the device at the beginning of labor.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, several sensors have been developed to improve herd management, as have methods to assess their performance [12,13]. Regarding the calving period, different strategies for imminent calving prediction have also been developed, such as automated remote sensors which can be fixed to the animal body to monitor the variation in behavior [14][15][16][17], rumination measures [18][19][20], body temperature [21,22] and tail movement [23,24] around calving. Information from these wearable sensors could be combined in machine-learning algorithms to refine their precision [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one gentle pushing (cow 8; time slot t − 16 to t − 12) and one head butting (cow 5; time slot t + 8 to t + 12) were observed as agonistic social interactions. Compared to the pre-sensor time slots, less social interaction was observed in the post-sensor time slots in five cows (1,4,6,7,9) and more social interaction was observed in four cows (2,3,5,8). However, Wilcoxon testing did not indicate any significant mean differences between the respective compared pre-and post-sensor time slots (see Figure 3).…”
Section: Social Interactionmentioning
confidence: 86%
“…Parameters such as activity, temperature, or rumination are used for this purpose. The available literature shows that some sensors on the market have the potential to achieve satisfying results in the early detection of calving [5][6][7][8][9]. Studies on tail-attached sensors have reported sensitivities of up to 95% [5].…”
Section: Introduction 1sensor Systems To Improve Calving Managementmentioning
confidence: 99%